Neck moment response characterization of restrained child occupant at standard test impact speed 24.4 km/h - Shasthri, Sevaguru; Venkatason, Kausalyah; Shah, Qasim Hussain; Abdullah, Kassim Abdulrahman; Idres, Moumen; Wong, Sha Voon (Maxwell Scientific Organization, 2014)
The effects of bullet vehicle crash impact angle, child restraint system design and restraint harness slack at standard test side impact speed of 24.4 km/h (15 mph) on moments sustained at the neck by a three year old child is investigated. A statistical methodology employing the Design of Experiments is adopted in this study whereby a Latin Hypercube Sampling is chosen as the experiment design. Mathematical models are built using the Response Surface Method based on simulation results whereby, good fitness is achieved. The singular and cross interactive effect of each predictor on the neck moment is analyzed. The number of significant parameters affecting the Neck Moment is shown to be largest for wide impact angles (ϕ≥60°). The vehicle impact angle parameter is revealed to be the largely the most sensitive parameter and on which all the other remaining parameters are highly dependent on. An ideal safe range for low neck moments has been established to be within ϕ angles 42° and 60°. The vehicle impact angle parameter is shown to be proportional to neck moments for wide impact angles, while it behaves inversely proportional to neck moments for narrow impact angles. The other parameters are generally found to be moderately significant only for wide impact angles. The harness friction coefficient is shown to hold relatively very little influence on neck moments.